Analysis and Design of Web-Based Vehicle Management Information Systems to Support Operational Efficiency - Abdul Khaliq; Ruly Dwi Arista; Arpan (Yayasan Sinergi Multidimensi Kreatif, 2025)
Operational efficiency is a top priority for organizations, with effective vehicle management being a crucial component. This research analyzes and designs a web-based Vehicle Management Information System aimed at optimizing vehicle utilization, reducing operational costs, and enhancing accountability. Addressing the problem of error-prone manual fiscal depreciation calculations, this system is designed to automate the process, ensuring greater accuracy and traceability. System analysis is conducted through visual modeling using the Unified Modeling Language (UML). The Activity Diagram maps the workflow of various user roles (Administrator, Operational Staff, Manager) in managing vehicle data, inputting usage and costs, and scheduling services. The Sequence Diagram further details the message interactions between system components (users, system, database) for each core functionality. Meanwhile, the Class Diagram presents the static structure of the system, defining key entities such as User, Vehicle, OperationalCost, Usage, Depreciation, and ServiceSchedule, along with their attributes and relationships. This system is designed for implementation using web-based frameworks like Laravel or CodeIgniter, adhering to the Model-View-Controller (MVC) architecture. This approach is chosen to ensure modularity, ease of maintenance, and enhanced system security. Consequently, the proposed system is expected to provide accurate and timely information, significantly supporting operational efficiency in the management of organizational vehicle assets.